Implementasi Kebijakan Peraturan Bupati Kabupaten Garut No 50 Tahun 2016 Tentang Tupoksi Dinas Sosial Dalam Pembinaan Sosial (Pembinaan Anak Jalanan) di Kabupaten Garut - Riksa Raesalat; Farida Aliyati (Jurnal Pembangunan dan Kebijakan Publik, 2020)
This research is motivated by the negative impact of street children who carry out their activities on the streets that are disturbing the community in terms of the comfort of life in Garut district, especially in urban areas. Here the role of social services in street children is by fostering street children that make street children be directed and have good creativity, planting life principles and training training that is embedded in the development of street children. The purpose of this study is to find data and information about the population of street children in the district of garut in 2018 amounted to 25 and in 2019 amounted to 65 and how the coaching was carried out by the Garut district social sevice. In addition, the social service that cooperates with the PP Garut regency Satpol always monitors the condition of the street children in the Garut regency, especially in the city, so that the data collection has not been done by the Garut regency office or it can be called street child supervision. Based on the research, it can be concluded that the social service in conducting tupoksi is based on the regent's regulation no 50/2016 on tupoksi on the social development of street children.